2019
DOI: 10.11114/ijsss.v7i6.4527
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual and Secular Existential Meaning-Making Coping Methods among Japanese Cancer Patients

Abstract: The present article is written on the basis of a sociological international project on meaning-making coping. The aim of the project has been to understand the role of culture in meaning-making coping. The project embarrasses studies among cancer patients in 10 countries. The present article is confined to the results obtained in the study in japan. The main aim was to investigate the impact of culture from a sociological perspective on the choice of coping methods. Twelve participants with various kinds of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…The findings of several studies (Ahmadi & Ahmadi, 2018;Cetrez et al, 2020;Ahmadi et al, 2018a;Ahmadi et al, 2018b;Ahmadi et al, 2017;Ahmadi et al, 2016a;Ahmadi et al, 2016b;Ahmadi et al, 2019a;Ahmadi et al, 2019b) confirm the third way, i.e. "culture affects selection of the strategies that an individual uses in any given situation."…”
Section: Secular Spiritual Religiousmentioning
confidence: 88%
See 1 more Smart Citation
“…The findings of several studies (Ahmadi & Ahmadi, 2018;Cetrez et al, 2020;Ahmadi et al, 2018a;Ahmadi et al, 2018b;Ahmadi et al, 2017;Ahmadi et al, 2016a;Ahmadi et al, 2016b;Ahmadi et al, 2019a;Ahmadi et al, 2019b) confirm the third way, i.e. "culture affects selection of the strategies that an individual uses in any given situation."…”
Section: Secular Spiritual Religiousmentioning
confidence: 88%
“…In our studies, sanctification of nature is found among Swedish and Malaysian cancer patients (Ahmadi et al, 2018a), sanctification of family and relationships among Chinese, Turkish and Malaysian cancer patients (Ahmadi & Ahmadi, 2018), sanctification of mountains and food among South Korean cancer patients (Ahmadi et al, 2017a;Ahmadi et al, 2016a;Ahmadi & Ahmadi, 2018), sanctification of music among Swedish and Chinese cancer patients (Ahmadi & Ahmadi, 2018), and sanctification of oneself among Swedish, Turkish and Malaysian cancer patients (Ahmadi et al, 2016b;Ahmadi et al, 2017b;Ahmadi et al, 2018a;Ahmadi et al, 2018b;Ahmadi & Ahmadi, 2018). Feelings of empathy seemed to bring about the sanctification of suffering people among Swedish and Turkish cancer patients (Ahmadi & Ahmadi, 2018;Ahmadi et al, 2018a), and sanctification of moments/positive solitude is found among Swedish cancer patients (Ahmadi, 2015;Ahmadi & Ahmadi, 2018) and sanctification of connectedness with deceased ancestors (Ahmadi et al, 2019a).…”
Section: Our View Of Sacred Mattersmentioning
confidence: 99%